Differential protease expression by cutaneous squamous and basal cell carcinomas. - A P Sappino; D Belin; J Huarte; S Hirschel-Scholz; J H Saurat; J D Vassalli (The Journal of Clinical Investigation, 1991)
To assess the postulated role of plasminogen activation in tumor invasion, we have investigated the cellular sites of synthesis for urokinase-type (uPA) and tissue-type (tPA) plasminogen activators and their inhibitors (PAI-1 and PAI-2) in two human cutaneous neoplasia that differ in their metastatic potential. The combined use of zymography on tissue sections and in situ hybridization demonstrates that uPA is produced by malignant cells of squamous cell carcinomas (SCC) but not by basal cell carcinomas (BCC), whereas tPA is detected exclusively in nonmalignant dermal tissue. In addition, we show that SCC neoplastic cells simultaneously produce variable amounts of PAI-1, and that PAI-1 production correlates inversely with uPA enzymatic activity. These observations establish that invasive human malignant cells in vivo can activate plasminogen through uPA production during the early phases of tumor growth; they also demonstrate that the proteolytic activity of tumor cells can be modulated by the concomitant production of PAI-1. Because SCC have a higher invasive and metastatic potential than BCC, our findings lend further support to the involvement of plasminogen activation in malignant behavior. Images